Stimulation of well SN-12 in the Seltjarnarnes low-temperature field in SW-Iceland - Tulinius, Helga; Axelsson, Gudni; Tomasson, Jens; Kristmannsdottir, Hrefna; Gudmundsson, Asgrimur (National Energy Authority, Grensasvegur, Reykjavik, IS, 1996)
Well SN-12 in the Seltjarnarnes low-temperature field in SW-Iceland was drilled to a depth of 2714 m in the fall of 1994. The well appeared to be almost non-productive at the end of drilling. A comprehensive ten day stimulation program was, therefore, initiated. The program involved, firstly, high-pressure wellhead injection and, secondly, high-pressure injection below a packer placed at 1412 m depth. After about twelve hours of wellhead stimulation the pressure dropped suddenly, indicating that the well had been stimulated. At the same time the water level response increased suddenly in two near-by monitoring wells. During the second stimulation phase (packer at 1412 m) the well appeared to be stimulated even further. The well eventually produced about 35 l/s with a drawdown of roughly 60 m, and the stimulation had increased the yield of the well by a factor of nearly 60. Thus well SN-12, which appeared to be almost non-productive at the completion of drilling, had turned into a good production well. It is believed that during the stimulation some previously closed fractures, or interbed contacts, reopened connecting well SN-12 to the main fracture system of the geothermal reservoir.